Foetal alcohol spectrum disorder: Effective helping responses from social workers. (July 2020) - Gibbs, Anita; Bagley, Kerryn; Badry, Dorothy; Gollner, Vicky
Foetal alcohol spectrum disorder (FASD) is a lifelong neurodevelopmental disability that often requires extensive intervention and support from the helping professions, notably social work. This article considers why a social work response to FASD is needed and explores social work frameworks and models that underpin current FASD-informed practice. It illustrates the discussion with three international models used in Canada and New Zealand, the Key Worker model, the Communities of Practice model and an advocacy and mentoring model.